Stimulating Financial-Fiscal Instruments of Supporting Development of Renewable Energy Sources: Bibliometric Analysis - Alla Moroz; Serhiy Lyeonov (Financial Markets, Institutions and Risks)
The transition to renewable energy sources is imperative for addressing global challenges such as climate change, energy security, and sustainable economic development. Financial-fiscal instruments, including subsidies, carbon pricing, green bonds, and tradable green certificates, have emerged as critical mechanisms to overcome economic and market barriers that impede renewable energy adoption. This study provides a comprehensive bibliometric analysis to explore the evolution, thematic focus, and global collaboration patterns in research on financial-fiscal mechanisms supporting renewable energy development, covering the period from 1972 to 2025. The aim of this research is to identify key trends, influential contributions, and emerging themes within the field, offering actionable insights for policymakers and researchers. The study employs bibliometric analysis, using the Scopus database as the primary data source. Analytical techniques, including keyword co-occurrence networks, thematic mapping, and collaboration trend analysis, were performed using R Studio’s Biblioshiny tool. The dataset comprised publications spanning five decades, enabling a robust exploration of the research landscape. The results highlight a steady annual growth rate of over 7% in publications, reflecting heightened academic and policy interest in financial-fiscal tools for renewable energy. Dominant research themes identified include carbon pricing, subsidies, green bonds, and technological innovation, which collectively underscore the integrative role of fiscal mechanisms in driving renewable energy transitions. Regional analysis reveals Europe and North America as leading contributors to the research field, with increasing participation from developing economies, particularly in Asia and Africa. Emerging financial mechanisms, such as green bonds and climate funds, were noted for their critical role in mobilizing private capital and reducing investment risks in renewable energy projects. The study also emphasizes the persistent challenges faced by developing nations, including limited access to financing, grid infrastructure constraints, and policy instability, and highlights the effectiveness of tailored fiscal measures like concessional loans and grants in addressing these barriers. This research contributes to the understanding of the dynamic evolution of financial-fiscal instruments in renewable energy development. It provides empirical evidence supporting their critical role in fostering sustainable energy systems and highlights areas for future research and policy refinement to accelerate the global energy transition. By leveraging these insights, policymakers and researchers can enhance the design and implementation of fiscal tools to achieve global climate and sustainability goals.